2021
DOI: 10.3390/ani11030741
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interleukin-7 on In Vitro Maturation of Porcine Cumulus-Oocyte Complexes and Subsequent Developmental Potential after Parthenogenetic Activation

Abstract: Interleukin-7 (IL-7) is a cytokine essential for cell development, proliferation and survival. However, its role in oocyte maturation is largely unknown. To investigate the effects of IL-7 on the in vitro maturation (IVM) of porcine oocytes, we analyzed nuclear maturation, intracellular glutathione (GSH) and reactive oxygen species (ROS) levels, and subsequent embryonic developmental competence after parthenogenetic activation (PA) under several concentrations of IL-7. After IVM, IL-7 treated groups showed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
(24 reference statements)
1
7
0
Order By: Relevance
“…IL-7 treatment regulates oxidative stress (21). Consistent with the results of the present study, we observed that IL-7 supplementation during porcine IVC increased intracellular GSH levels and reduced ROS levels in 4-cell embryos, provoking ZGA.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…IL-7 treatment regulates oxidative stress (21). Consistent with the results of the present study, we observed that IL-7 supplementation during porcine IVC increased intracellular GSH levels and reduced ROS levels in 4-cell embryos, provoking ZGA.…”
Section: Discussionsupporting
confidence: 92%
“…IL-7 was also identified as a potential candidate for oocyte quality screening tests ( 22 ). Recently as well, it was demonstrated that IL-7 improves oocyte maturation and developmental potential via the regulation of apoptosis-related genes when administered within an IVM system for sheep ( 40 ) and pigs ( 21 ). Thus, we speculated that IL-7 possibly plays a similar role in porcine IVC, and in this regard, our results demonstrated that IL-7 treatment favored the in vitro development of porcine preimplantation embryos after PA, and reduced fragmentation in day 2 embryos.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to many other studies [33][34][35], this study showed that ROS was upregulated, and oxidative stress was induced in porcine oocytes as a result of rotenone treatment. In the previous study [36][37][38], GSH detected using Cell Tracker was the opposite concept of ROS, and the rotenone treated group decreased compared to the control group. As oxidative stress was speculated to be the result of rotenonemediated suppression of mitochondrial function, mitochondrial function was also investigated.…”
Section: Discussionmentioning
confidence: 84%